2009
DOI: 10.1090/s0002-9939-09-09789-5
|View full text |Cite
|
Sign up to set email alerts
|

The size of isoperimetric surfaces in $3$-manifolds and a rigidity result for the upper hemisphere

Abstract: Abstract. We characterize the standard S 3 as the closed Ricci-positive 3-manifold with scalar curvature at least 6 having isoperimetric surfaces of largest area: 4π. As a corollary we answer in the affirmative an interesting special case of a conjecture of M. Min-Oo's on the scalar curvature rigidity of the upper hemisphere.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 15 publications
1
16
0
3
Order By: Relevance
“…If g has positive Ricci curvature and scalar curvature R ≥ 6, the 4π upper bound on the supremum of the left-hand-side of the above expression was previously obtained by Eichmair [12]. We observed that the supremum of the isoperimetric profiles of the examples that we use also form an unbounded sequence.…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…If g has positive Ricci curvature and scalar curvature R ≥ 6, the 4π upper bound on the supremum of the left-hand-side of the above expression was previously obtained by Eichmair [12]. We observed that the supremum of the isoperimetric profiles of the examples that we use also form an unbounded sequence.…”
Section: Introductionsupporting
confidence: 64%
“…Since the proof of the positive mass conjecture in general relativity by Schoen and Yau [23], and Witten [26], the rigidity phenomena involving the scalar curvature has been fascinating the geometers. These results play an important role in modern differential geometry and there is a vast literature about it, see ( [1,3,4,5,6,7,8,12,15,16,17,18,19,22]). Many of these works concern rigidity phenomena involving the scalar curvature and the area of minimal surfaces of some kind in three-manifolds.…”
Section: Introductionmentioning
confidence: 97%
“…It is well-known that lower bounds on the scalar curvature of M give some information on the space of minimal surfaces. Several rigidity theorems have been obtained assuming the existence of an area-minimizing surface of some kind ( [3], [4], [7], [13], [25], [34]), but no known result asserts rigidity under the presence of a minimal surface produced by min-max methods. In this paper we prove theorems in that direction.…”
Section: Introductionmentioning
confidence: 99%
“…Cependant, dans un travail récent [1], Brendle, Marques et Neves construisent, pour n ≥ 3, des métriques sur l'hémisphère à courbure scalaire strictement supérieure à n(n − 1) satisfaisant les conditions (2) et (3). De tels exemples mettent donc en défaut la validité de l'énoncé de Min-Oo.…”
Section: Introductionunclassified
“…Dans [10], Hang et Wang montrent qu'en remplaçant l'hypothèse (1) sur la courbure scalaire par son analogue sur la courbure de Ricci, la conjecture est vérifiée. Le cas de la dimension 3 est traité dans [3] avec des conditions supplémentaires sur le profil isopérimétrique de ∂ M. Dans un autre travail [9], Hang et Wang s'intéressent aux déformations conformes des métriques sur l'hémisphère standard et ils prouvent en particulier la conjecture pour ce type de transformations. Plus précisément, ils montrent: Théoréme 1 ([9]) Soit g = e 2u g st une métrique dans la classe conforme de la métrique ronde g st à courbure scalaire R g ≥ n(n − 1).…”
Section: Introductionunclassified